2016
DOI: 10.1088/1367-2630/18/10/103024
|View full text |Cite|
|
Sign up to set email alerts
|

The valley filter efficiency of monolayer graphene and bilayer graphene line defect model

Abstract: Figure 3. The performance of model I in the presence of disorder. The results for Anderson (long range) disorder is exhibited in a1-f1 (a2-f2). The other parameters are d=20 and M=100. AbstractIn addition to electron charge and spin, novel materials host another degree of freedom, the valley. For a junction composed of valley filter sandwiched by two normal terminals, we focus on the valley efficiency under disorder with two valley filter models based on monolayer and bilayer graphene. Applying the transfe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
43
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 35 publications
(44 citation statements)
references
References 48 publications
(105 reference statements)
1
43
0
Order By: Relevance
“…Moreover, it was shown that the broken inversion symmetry results in the valley-dependent optical selection rule, which can be used to selectively excite carriers in the K or −K valley via right or left circularly polarized light, respectively 10,11 . Valley polarization can also be achieved in monolayer [12][13][14][15] and bilayer 15 graphene systems with barriers. In addition, proposals exploiting strain that induces pseudomagnetic fields acting oppositely in the two valleys 16,17 together with artificially induced carrier mass and spin-orbit coupling 18 have been put forward.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, it was shown that the broken inversion symmetry results in the valley-dependent optical selection rule, which can be used to selectively excite carriers in the K or −K valley via right or left circularly polarized light, respectively 10,11 . Valley polarization can also be achieved in monolayer [12][13][14][15] and bilayer 15 graphene systems with barriers. In addition, proposals exploiting strain that induces pseudomagnetic fields acting oppositely in the two valleys 16,17 together with artificially induced carrier mass and spin-orbit coupling 18 have been put forward.…”
Section: Introductionmentioning
confidence: 99%
“…15,21,25,26 Interestingly, it is recently noted that inter-valley scattering can provide a useful resource for valleytronics, besides its well anticipated role in depolarizing valley. 26 In 1D systems, it is shown that inter-valley scattering by disorders can realize a distinct valleytronic functionality, the valley source, where upon passing charge current, valley currents are pumped in both the forward and backward directions, with a net outward valley flux (c.f.…”
Section: -25mentioning
confidence: 99%
“…They hybridized SiNRs with different topological phases and found the topological valley edge states appeared at the interface between two different topological insulator phases. We have to mention that the valley edge states, also known as the kink states in graphene systems [27,28] or photonic crystals [29,30]. However, the definition of kink states are narrower than the inner-edge states.…”
Section: Introductionmentioning
confidence: 99%